Effects of exogenous spraying of melatonin on the growth of Platycrater arguta under drought stress - Xule Zhang; Xiaohua Ma; Yaping Hu; Qingdi Hu; Junxiu Wen; Yizeng Chen; Renjuan Qian; Jian Zheng (Frontiers in Plant Science)
Platycrater arguta is a rare and endangered deciduous shrub originating from the Tertiary Period. Understanding its drought tolerance is crucial for conservation efforts and enhancing its resilience to environmental stress. This study aimed to assess the effects of varying levels of drought stress on the phenotype and physiological–biochemical characteristics of P. arguta. The study subjected P. arguta to different levels of drought stress using 10%, 20%, and 30% polyethylene glycol-6000 (PEG-6000) over a 10-day period. Additionally, the effects of exogenous melatonin application at various concentrations (including 100 µM) were examined to determine its potential in alleviating drought-induced damage. Key parameters measured included leaf relative water content, net photosynthetic rate (Pn), antioxidant enzyme activity, and soluble sugar content. Drought stress significantly inhibited the growth of P. arguta. As PEG-6000 concentration increased, leaf relative water content and net photosynthetic rate decreased, while leaf wilting severity, membrane damage, antioxidant enzyme activity, and soluble sugar content increased. A 30% PEG-6000 concentration caused irreversible damage, leading to plant death. Exogenous application of 100 µM melatonin alleviated this damage by increasing leaf relative water content, enhancing photosynthetic efficiency, boosting antioxidant enzyme activity, accumulating osmotic regulators, and reducing leaf desiccation. The study demonstrated that P. arguta is sensitive to severe drought conditions, with 30% PEG-6000 causing irreversible damage. However, the application of 100 µM melatonin significantly improved the plant's drought tolerance by upregulating the expression of ABI1 and downregulating genes such as AUX1A-2, IAA2-2, and HP2-1. This finding highlights the potential of melatonin as a protective agent against drought stress, providing valuable insights for the conservation and enhancement of P. arguta's resilience to environmental challenges.